2022
DOI: 10.3389/fimmu.2022.1077768
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant metabolic processes promote the immunosuppressive microenvironment in multiple myeloma

Abstract: IntroductionMultiple myeloma (MM) is still an incurable plasma cell malignancy. The efficacy of immunotherapy on MM remains unsatisfactory, and the underlying molecular mechanisms still are not fully understood.MethodsIn this study, we delineated the dynamic features of immune cell in MM bone marrow (BM) along with elevated tumor cell infiltration by single-cell RNA sequencing (scRNA-seq), and investigated the underlying mechanisms on dysfunction of immune cells associated with myelomagenesis.ResultsWe found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 75 publications
(87 reference statements)
1
12
0
Order By: Relevance
“…However, the molecular characteristics and the underlying function of these WM cells have not been fully investigated. Highthroughput single-cell RNA sequencing (scRNA-seq) is a powerful approach for studying heterogeneous tissues and kinetics cellular processes [14,15]. Here, scRNA-seq analysis of BM mononuclear cells (BMNCs) from five newly diagnosed WM patients (NDWMs) and six healthy donors (HDs) were studied, and the heterogeneity of WM cells and non-malignant cells in the BM microenvironment was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…However, the molecular characteristics and the underlying function of these WM cells have not been fully investigated. Highthroughput single-cell RNA sequencing (scRNA-seq) is a powerful approach for studying heterogeneous tissues and kinetics cellular processes [14,15]. Here, scRNA-seq analysis of BM mononuclear cells (BMNCs) from five newly diagnosed WM patients (NDWMs) and six healthy donors (HDs) were studied, and the heterogeneity of WM cells and non-malignant cells in the BM microenvironment was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Trms constitute a Tm population that enters infected tissues during the effector phase of the immune response, ceasing direct involvement in the immune response within the circulatory system but counteracting renewed antigenic attack on local tissue 29 . A study of the aberrant metabolic microenvironment in the context of multiple myeloma revealed that CD69+STMN1+CD62L–CD8+ Trm cell‐related TCA cycle activity and amino acid metabolism were impaired, whereas glycolysis and FAO were enhanced, 91 corroborating the pivotal effect of FAO on immune memory mediated by Trms within the TME. More critically, in addition to providing energy support, fatty acid metabolism ensures maintenance of the nicotinamide adenine dinucleotide phosphate(NADPH) and ATP levels in Trms to safeguard them against reactive oxygen species (ROS) peroxidation 92 .…”
Section: T‐cell Metabolic Reprogramming and Related Antitumour Immune...mentioning
confidence: 99%
“…PIM kinase, a member of the serine/threonine kinase family, controls the phosphorylation of various proteins involved in cellular metabolism and survival and is closely associated with mTORC1 signalling activity to influence CD8+ T‐cell memory state formation 170 . The pan inhibitor of the PIM kinase AZD1208 inhibits mTOR signalling activity, preventing ROS interference with CD8+ Teff mitochondrial metabolism and restoring amino acid transport, thereby increasing CD8+ T‐cell toxicity and promoting Tm proliferation and persistence 91 . In addition, metformin phosphorylates AMPK to downregulate mTORC1 and induce the glycolysis‐dependent conversion of CD8+ T cells to FAO, contributing to enhanced acquisition of a memory phenotype and prolonged cell survival 155,149 .…”
Section: Therapeutic Advances In Targeting T‐cell Metabolic Processesmentioning
confidence: 99%
“…Another study assessed serine synthesis on MM progression, demonstrating that the increase of serine synthesis was related to the proliferation of MM cells, and higher expression of the related gene PHGDH was associated with a poor prognosis of MM [ 50 ]. Furthermore, abnormal amino acid metabolism promoted MM progression through the immunosuppressive microenvironment [ 51 ].…”
Section: Abnormal Amino Acid Metabolism and Multiple Myelomamentioning
confidence: 99%